Heterogeneous marine environments diversify microbial-driven polymetallic nodule formation in the South China Sea - Lai, Mingyan; Liu, Qian; Wang, Xiaogu; Sun, Dong; Ran, Lihua; Li, Xiaohu; Yang, Chenghao; Lu, Bo; Xu, Xue-Wei; Wang, Chun-Sheng (Frontiers in Marine Science, 2024)
Most studies on the genesis of polymetallic nodules suggested that nodules in the South China Sea (SCS) are hydrogenetic; however, the complexity and the heterogeneity in hydrology and geochemistry of the SCS might cause different processes of nodule formation, impacting their application and economic value. Microbial-mediated ferromanganese deposition is an important process in nodule formation, but the related microbial potentials are still unclear in the SCS. In this study, we sampled in three typical regions (A, B, and C) of the SCS enriched with polymetallic nodules. Firstly, we investigated environmental and microbial characteristics of the water columns to determine the heterogeneity of upper seawater that directly influenced deep-sea environments. Then, microbial compositions and structures in sediment cores, overlying waters, and nodules (inside and outside) collected within the same region were analyzed for inferring features of nodule environments. Microbial interactions between nodules and surrounding environments were estimated with collinear network analysis. The microbial evidence indicated that geochemical characteristics in deep sea of the SCS that were key to the polymetallic nodule formation were severely affected by organic matter flux from upper water column. The sediment in region A was sub-oxic due to the large input of terrigenous and phytoplankton-derived organic matter, potentially enhancing the overflow of reduced metals from the porewater. The intense microbial interaction between nodules and surface sediment reinforced the origin of metals for the ferromanganese deposition from the sediment (diagenetic type). Contrarily, the sediments in regions B and C were relatively rich in oxygen, and metal ions could be majorly supplied from seawater (hydrogenetic type). The large discrepancy in microbial communities between nodule inside and remaining samples suggested that nodules experienced a long-term formation process, consistent with the feature of hydrogenetic nodules. Overall, distributions and interactions of microbial communities in nodules and surrounding environments significantly contributed to the nodule formation in the SCS by manipulating biogeochemical processes that eventually determined the source and the fate of metal ions.